2019
DOI: 10.1038/s41596-018-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Using enhanced number and brightness to measure protein oligomerization dynamics in live cells

Abstract: This Protocol describes enhanced Number and Brightness (eN&B), an approach that uses fluorescence fluctuation spectroscopy data to directly measure the oligomerisation state and dynamics of fluorescently-tagged proteins in living cells.TWEET Detecting protein oligomerisation states and dynamics in live cells using enhanced Number and Brightness (eN&B). COVER TEASER Detecting oligomerisation dynamics in live cellsUp to three primary research articles where the protocol has been used and/or developed: 1. Ojosneg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 95 publications
(128 reference statements)
0
35
0
Order By: Relevance
“…Although SpIDA has many useful attributes (21), as for related methods including Number and Brightness analysis (29) and Photon Counting Histogram (30), it only provides information on the average size of oligomers within potentially complex mixtures of oligomers of different sizes and also may be sensitive to brighter inhomogeneities in the fluorescence images. To overcome these issues we recently developed a new approach described as 1-and 2-dimensional Fluorescence Intensity Fluctuation (FIF) spectrometry (22,23).…”
Section: Fluorescence Intensity Fluctuation (Fif) Spectrometry Reinfomentioning
confidence: 99%
“…Although SpIDA has many useful attributes (21), as for related methods including Number and Brightness analysis (29) and Photon Counting Histogram (30), it only provides information on the average size of oligomers within potentially complex mixtures of oligomers of different sizes and also may be sensitive to brighter inhomogeneities in the fluorescence images. To overcome these issues we recently developed a new approach described as 1-and 2-dimensional Fluorescence Intensity Fluctuation (FIF) spectrometry (22,23).…”
Section: Fluorescence Intensity Fluctuation (Fif) Spectrometry Reinfomentioning
confidence: 99%
“…The fluctuation intensity ( F ( t )) was further extracted through photon counting histogram analysis (Figure S4D‐F). Compared with the effect of laser pulse energy on the intensity of R6G fluorescence, the TPL intensity of AuNR and AuNR‐RB were enhanced as the laser pulse energy increased. And then, the average number of emissive species (1/˂ N ˃) yielded from the amplitude of autocorrelation function also suggested that the number of emissive species in R6G solution was not affected by the laser pulse energy (Figure S4G).…”
Section: Resultsmentioning
confidence: 99%
“…Hortiguela et al developed a statistical resampling of raw fluctuation data to measure coexisting oligomer species in each pixel and this improved N&B methodology is called enhanced N&B analysis (eN&B) [154,155]. One drawback to eN&B is analysis requires 200 frames and can take from seconds to minutes to complete one timepoint.…”
Section: Number and Brightness (Nandb) Analysismentioning
confidence: 99%
“…sliding window, and the exponential filtering method [143]. Filtering algorithms were applied to imaging FFT data to remove contributions from cellular movement or photobleaching and thus enhance the accuracy of the calculated molecular parameters [140,143,155,173]. Lange et al used a wavelet shrinking algorithm to reduce the false positive signal from 69% to 4% for the negative control in FCCS measurements [174].…”
Section: Advantages and Disadvantages Of Fftsmentioning
confidence: 99%